Clinical and radiographic evaluation of results of MTA pulpotomy and laser-assisted MTA pulpotomy - C Swarnalatha; J Suresh Babu; Pratyaksha S Panwar; Mohammad Abdullah Alquraishi; Saleh Ali Almalaq; Fahad Abdulrahman Alnasrallah; Abhishek Singh Nayyar (Wolters Kluwer Medknow Publications, 2020)
Introduction: The present in vivo study was carried out to compare the clinical and radiographic success rates of mineral trioxide aggregate (MTA) pulpotomy and laser-assisted MTA pulpotomy in human primary molars. Materials and Methods: The present study was a randomized clinical trial in design, wherein forty human primary teeth requiring pulpotomy treatment which met the selection criteria (clinical and radiographic) were divided into two groups, Group 1 (n = 20) wherein the pulpotomy was performed with MTA alone and Group 2 (n = 20) wherein laser-assisted pulpotomy was performed with diode laser-assisted MTA (L-MTA). The patients were recalled after 3, 6 and 9 months, respectively, and evaluated clinically and radiographically. Data were analyzed statistically, while P< 0.05 was considered statistically significant. Results: The clinical success rate in the MTA group was 90%, 84.21%, and 88.23% at 3, 6, and 9 months, respectively, with no clinical signs or symptoms reported at the said follow-up visits, while the radiographic success rate was found to be 85%, 84.21%, and 82.3%, respectively. On the contrary, the clinical success rate in the L-MTA group was found to be 95%, 94.74%, and 94.44% at 3, 6, and 9 months, respectively, with the radiographic success rate reported being 90%, 89.47%, and 88.89%, respectively. Conclusion: The combination of diode laser and MTA yielded better clinical and radiographic success rates over the pulpotomy procedures done with the help of MTA alone, thereby, concluding that lasers may be considered as adjuvant alternatives for vital pulp therapy on human primary teeth.